Atovaquone/proguanil therapy for Plasmodium falciparum and Plasmodium vivax malaria in Indonesians who lack clinical immunity. - Lacy, MD; Maguire, J; Barcus, M; Ling, J; Bangs, M; Gramzinski, R; Basri, H; Sismadi, P; Miller, G; Chulay, J; Fryauff, D; Hoffman, S; et al. (2002)
Thirty-eight of 295 subjects participating in a randomized, double-blind, placebo-controlled trial of the efficacy of daily administration of atovaquone/proguanil for malaria prevention developed malaria at some time during the 20-week prophylaxis period. These subjects (3 atovaquone/proguanil recipients and 35 placebo recipients) were treated with 4 tablets of atovaquone/proguanil per day for 3 days. Atovaquone/proguanil provided safe, well-tolerated, and effective therapy for uncomplicated malaria in nonimmune Indonesians.